Investigation on the effect of process parameters on mechanical and microstructural properties of AA8011 similar FSW weld joints. (July 2022) - Chakravarthi, Gurijala; Giridharan, Krishan; Stalin, Balasubramaniam; Padmanabhan, Sambandam; Sekar, Subramani; Nagaprasad, Nagaraj; Jule, Leta Tesfaye; Krishnaraj, Ramaswamy
Friction stir welding (FSW) factors significantly impact the welding characteristics of AA 8011 and similar alloys weld joints produced by FSW. The tool pin profiles influence joint characteristics, weld quality, and joint strength. This study used three tool pin profiles to create weld connections at three different tool rotation rates and various welding speeds. Design of experiments (DOE) was utilized to execute complete full factorial experiments. The welded joints' mechanical characteristics were examined using hardness and tensile tests at room temperature. The average maximum hardness number was 38.28 HRB with the tapered tool at 1300 rpm spindle speed and welding speed of 20 mm/min at 5 kN unvarying axial force of the whole operation. The lowest hardness value was 30 HRB using a taper threaded pin profile tool, rotating at 1200 rpm and welding at 60 mm/min. When the taper pin profile tool was used at 1500 rpm, the highest tensile strength of the weld joint was achieved, which was the closest value of the parent material. At the same welding speed of 20 mm/min, the taper threaded pin tool at 1300 rpm produces the lowest tensile strength of 84.16 MPa, made utilizing a taper threaded pin tool.